Therapeutic performances of some selected aqua drugs - Md. Rasheduzzaman Khan Dipu; Md. Bazlur Rashid Chowdhury; Mohammad Abdullah Al Imran; Md. Abdul Quaiyum; Md. Tareq-Uz-Zaman (Journal of Fisheries, 2014)
This study was carried out at the Disease Laboratory of the Faculty of Fisheries, Bangladesh Agricultural University, Mymensingh, Bangladesh to verify the therapeutic performances of six commercial aqua drugs; three doses were selected as less than recommended, recommended and more than recommended to assess their performances. Before starting therapeutic experimental nine climbing perch (Anabas testudineus) and six stinging catfish (Heteropneustes fossilis) were confirmed as diseased ones by their clinical signs. The backswimmers (Notonecta glauca) were collected from faculty of fisheries pond and fish louses (Argulus sp.) were collected from tilapia fishes. Effective doses and their performances were determined on the basis of desired water quality change and clinical signs. It was found that all the drugs performed better at more than recommended doses as follows Aqua Ox performed better at the rate of 0.2 mg/l, GR Plus, 0.0005 ml/l, ID Plus (5%), 0.00026 ml/l; Active Blue, 0.0002 ml/l; Hashpoka Killer, 0.0001 ml/l; and Para Control, 0.001 ml/l. So these doses were suggested as recommended doses.